THE IMPLEMENTATION OF THE MUDHARABAH PRINCIPLE IN THE WORKING CAPITAL FINANCING SCHEME OF THE AMANAH NEGERI SEJAHTERA SHARIA COOPERATIVE, CIANJUR - Yudih, Dadang (Universitas Suryakancana, 2025)
Penelitian ini bertujuan untuk menganalisis penerapan prinsip Mudharabah pada skema pembiayaan modal kerja di Koperasi Syariah Amanah Negeri Sejahtera Cianjur. Pendekatan penelitian yang digunakan adalah deskriptif kualitatif dengan pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi. Subjek penelitian meliputi pengurus koperasi dan anggota penerima pembiayaan Mudharabah. Analisis data dilakukan dengan model interaktif Miles dan Huberman yang mencakup reduksi data, penyajian data, serta penarikan kesimpulan dan verifikasi. Hasil penelitian menunjukkan bahwa pelaksanaan akad Mudharabah di koperasi telah sesuai dengan prinsip-prinsip syariah, di mana pembagian nisbah bagi hasil dilakukan berdasarkan kesepakatan bersama tanpa mengandung unsur riba, gharar, maupun maysir. Dalam praktiknya, koperasi bertindak sebagai shahibul maal dan anggota sebagai mudharib, dengan tujuan meningkatkan produktivitas dan kesejahteraan ekonomi anggota. Penerapan akad ini memberikan dampak positif terhadap peningkatan kinerja usaha, seperti bertambahnya modal, omzet, dan kesadaran berwirausaha syariah di kalangan anggota. Faktor pendukung implementasi meliputi kepercayaan anggota, dukungan manajemen, serta pengawasan aktif dari Dewan Pengawas Syariah. Adapun hambatan yang ditemui adalah keterbatasan pemahaman anggota terhadap akad Mudharabah dan risiko moral hazard. Secara keseluruhan, penerapan Mudharabah di koperasi ini terbukti mampu menjadi instrumen pembiayaan berbasis syariah yang adil, transparan, dan mendukung pertumbuhan ekonomi umat. This study aims to analyze the implementation of the Mudharabah principle in the working capital financing scheme at the Amanah Negeri Sejahtera Sharia Cooperative in Cianjur. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. The research subjects included cooperative management and members receiving Mudharabah financing. Data analysis was conducted using the interactive model of Miles and Huberman, which consists of data reduction, data presentation, and conclusion drawing/verification. The results show that the implementation of the Mudharabah contract at the cooperative aligns with Sharia principles, where the profit-sharing ratio (nisbah) is determined based on mutual agreement without involving elements of riba (usury), gharar (uncertainty), or maysir (gambling). In practice, the cooperative acts as the shahibul maal (capital provider), while members serve as the mudharib (entrepreneur), with the aim of enhancing members’ productivity and economic welfare. The application of this contract has had a positive impact on improving business performance, such as increasing capital, turnover, and awareness of Sharia-based entrepreneurship among members. Supporting factors include members’ trust, management support, and active supervision by the Sharia Supervisory Board. However, obstacles identified include limited understanding of the Mudharabah contract among members and moral hazard risks. Overall, the implementation of Mudharabah in this cooperative has proven to be an equitable and transparent Sharia-based financing instrument that supports the economic growth of the Muslim community.